Differentiation of Methanosaeta concilii and Methanosarcina barkeri in Anaerobic Mesophilic Granular Sludge by Fluorescent In Situ Hybridization and Confocal Scanning Laser Microscopy - Rocheleau, Sylvie (American Society for Microbiology, 1999)
Oligonucleotide probes, designed from genes coding for 16S rRNA, were developed to differentiate Methanosaeta concilii, Methanosarcina barkeri, and mesophilic methanogens. All M. concilii oligonucleotide probes (designated MS1, MS2, and MS5) hybridized specifically with the target DNA, but MS5 was the most specific M. concilii oligonucleotide probe. Methanosarcina barkeri oligonucleotide probes (designated MB1, MB3, and MB4) hybridized with different Methanosarcina species. The MB4 probe specifically detected Methanosarcina barkeri, and the MB3 probe detected the presence of all mesophilic Methanosarcina species. These new oligonucleotide probes facilitated the identification, localization, and quantification of the specific relative abundance of M. concilii and Methanosarcina barkeri, which play important roles in methanogenesis. The combined use of fluorescent in situ hybridization with confocal scanning laser microscopy demonstrated that anaerobic granule topography depends on granule origin and feeding. Protein-fed granules showed no layered structure with a random distribution of M. concilii. In contrast, a layered structure developed in methanol-enriched granules, where M. barkeri growth was induced in an outer layer. This outer layer was followed by a layer composed of M. concilii, with an inner core of M. concilii and other bacteria.